Articaine pharmacokinetics in tumescent anaesthesia - Bruning, G.; Rasmussen, H.; Teichler, A.; Standl, T.; Moll, I. (Phlebologie, 2010)
Tumescence local anaesthesia (TLA) is being increasingly used in varicose vein surgery. However, this requires doses of local anaesthetics that exceed the licensed limits. Whilst data exist for lidocaine and prilocaine, the literature rarely contains those for the local anaesthetic articaine. Patients, methods: Postoperative levels of methaemoglobin as well as plasma concentrations of articaine hydrochloride (articaine HCl) and articaine acid were measured in 100 patients who underwent varicose vein surgery under TLA after subcutaneous infiltration of 2.86 to 19.56 mg articaine pro kg body weight. With the first 20 patients, several blood samples for each parameter were collected at two-hour intervals to construct the plasma concentration versus time curves. In the following 80 patients, the plasma concentrations of methaemoglobin (MetHb), articaine HCl and articaine acid were each measured once only at the time of the previously determined average peak. Patient satisfaction, pre-, intra- and postoperative pain were recorded with the aid of questionnaires and the visual analogue scale (VAS). Results: Maximum concentrations of articaine HCl (n = 100) in plasma were 0.0034 to 0.5800 μg/ml (median: 0.0517 μg/ml) and were observed one hour after the start of infiltration. Values considered toxicologically harmful are >5 μg/ml. Levels of MetHb ranged from 0.19 to 1.90% (median: 0.78%) and were always normal. The median score on the VAS for the pain caused by TLA and the operation was 5 (0–10; n =4 3). Preoperative administration of 500 mg ibuprofen reduced the score to 3 (0–10; n = 40). Ibuprofen was well tolerated by the patients. Without ibuprofen, the patients were free of post-operative pain for 2 hours (0–10), while with ibuprofen, they were pain-free for 3.0 hours (0.5–9). Patient satisfaction was extremely high. 91.75% would agree to the same stripping operation being carried out in the same way again. Plasma concentrations of articaine acid, as the inert product of articaine HCl metabolism, peaked after 8 hours and were between 0.92 and 14.58 μg/ml (median: 3.95 μg/ml). Conclusion: The use of doses of up to 20 mg/kg body weight articaine in TLA appears to be a safe technique with high patient satisfaction. In comparison with prilocaine, the risk of methaemoglobinaemia is nil. Due to its structure, the use of articaine has none of the carcinogenic potential of the lidocaine metabolite, 2,6-dimethylalanine. The disadvantage of articaine is its rapid metabolism, which gives it a shorter duration of action and hence a shorter postoperative analgesia compared with prilocaine and lidocaine.
Keywords: Tumescence local anaesthesia; articaine; pharmacokinetics